Acetyl-11-Keto-Beta Boswellic Acid (AKBA) Protects Lens Epithelial Cells Against H2O2-Induced Oxidative Injury and Attenuates Cataract Progression by Activating Keap1/Nrf2/HO-1 Signaling - Yang, Tianke; Lin, Xiaolei; Li, Hongzhe; Zhou, Xiyue; Fan, Fan; Yang, Jianing; Luo, Yi; Liu, Xin (Frontiers in Pharmacology, 2022)
Age-related cataract (ARC) is one of the leading blinding eye diseases worldwide. Chronic oxidative stress and the apoptosis of human lens epithelial cells (HLECs) have been suggested to be the mechanism underlying cataract formation. Acetyl-11-keto-β-boswellic acid (AKBA) is a pentacyclic triterpene with antioxidative and antiapoptotic effects. In this study, we investigated the potential effects of AKBA on oxidative-induced HLECs injury and cataract formation. H2O2 was used to simulate HLECs oxidative injury in vitro, and Na2SeO3 was applied to establish an in vivo cataract model. In our current study, a cell counting kit-8 (CCK-8) assay was performed to evaluate the effects of H2O2 and AKBA on cell viability in vitro. Intracellular reactive oxygen species (ROS) levels were measured with the ROS assay to verify the antioxidant capacity of AKBA. Apoptotic cells were detected and measured by TUNEL staining and flow cytometry, and qRT-PCR and Western blotting were applied to examine the transcription and expression of apoptosis-related proteins. Furthermore, immunofluorescence staining was performed to locate factor-erythroid 2-related factor 2 (Nrf2), and the protein levels of Nrf2, kelch-like ECH-associated protein 1 (Keap1) and heme oxygenase-1 (HO-1) were determined by Western blotting. Finally, we observed the degree of lens opacity and performed hematoxylin-eosin (H&E) staining to assess the protective effect of AKBA on cataract formation in vivo. AKBA increased HLECs viability under H2O2 stimulation, decreased intracellular ROS levels and alleviated the cell apoptosis rate in vitro. AKBA significantly decreased the expression of caspase-3 and Bax and increased the content of Bcl-2. The results of immunofluorescence and immunohistochemical staining proved that the expression and nuclear translocation of Nrf2 were activated with AKBA treatment in vivo and in vitro. Moreover, computational docking results showed that AKBA could bind specifically to the predicted Keap1/Nrf2 binding sites. After AKBA activation, Nrf2 dissociates from the Nrf2/Keap1 complex, translocates into the nucleus, and subsequently promotes HO-1 expression. In addition, AKBA attenuated lens opacity in selenite-induced cataracts. Overall, these findings indicated that AKBA alleviated oxidative injury and cataract formation by activating the Keap1/Nrf2/HO 1 cascade. Therefore, our current study highlights that AKBA may serve as a promising treatment for ARC progression.